Quizas algo hermoso : [book with audioplayer] como el arte transformo un barrio - Campoy, F. Isabel; Howell, Theresa, 1974- ([Wonderbook collection]., 2019)
"Mira lives in a gray and hopeless urban community until a muralist arrives and, along with his paints and brushes, brings color, joy, and togetherness to Mira and her neighbors"--